2022
DOI: 10.1111/os.13288
|View full text |Cite
|
Sign up to set email alerts
|

A new cocktail formula with diprospan of local infiltration analgesia in primary total hip arthroplasty: A prospective, randomized, controlled, observer‐blinded study

Abstract: Objective This study aimed to observe the analgesic effect of the cocktail formulation with diprospan during total hip arthroplasty (THA). Methods From September 2018 to April 2019, 120 patients undergoing primary unilateral THA were included in this prospective, randomized, observer‐blinded study. Patients were randomized into three groups, according to the different local infiltration analgesia (LIA) strategies: LIA with ropivacaine (the ropivacaine group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Habib et al’s study 4 evaluated the effect of intra-articular diprospan on blood glucose levels in diabetic patients and concluded that patients belonging to diprospan group had significantly higher levels of blood glucose following intra-articular injection. In another study involving diprospan, Wang et al 5 aimed to observe the analgesic effects of a cocktail formula containing ropivacaine, morphine, and diprospan for local infiltration analgesia in total hip arthroplasty. Blood sugar levels were monitored as a part of their secondary outcomes; it was concluded that there was no significant fluctuation of glucose levels ( P = 1.000).…”
Section: To the Editormentioning
confidence: 99%
“…Habib et al’s study 4 evaluated the effect of intra-articular diprospan on blood glucose levels in diabetic patients and concluded that patients belonging to diprospan group had significantly higher levels of blood glucose following intra-articular injection. In another study involving diprospan, Wang et al 5 aimed to observe the analgesic effects of a cocktail formula containing ropivacaine, morphine, and diprospan for local infiltration analgesia in total hip arthroplasty. Blood sugar levels were monitored as a part of their secondary outcomes; it was concluded that there was no significant fluctuation of glucose levels ( P = 1.000).…”
Section: To the Editormentioning
confidence: 99%
“…A number of studies have selected different kinds of glucocorticoids as the formulations of drug mixes, such as betamethasone, triamcinolone, dexamethasone, etc [20,21] . So far, no one has determined which glucocorticoid in drug mixes is the best choice.…”
Section: Discussionmentioning
confidence: 99%
“…Periarticular infiltration analgesia (PIA) has been proposed as it can improve postoperative pain control and minimize the risk profile by reducing central nervous system sensitization, 3 thus lowering postoperative pain and opiate demand as well as improving short‐term range of motion (ROM) 4 . Although a variety of agents and compositions are available for periarticular injection, with varying analgesic effects, there is no golden standard regarding the ideal formula.…”
Section: Introductionmentioning
confidence: 99%